x2-10=-3x

Add 3x to both sides of the equation.

x2-10+3x=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -10 and whose sum is 3.

-2,5

Write the factored form using these integers.

(x-2)(x+5)=0

(x-2)(x+5)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x-2=0

x+5=0

Set the first factor equal to 0.

x-2=0

Add 2 to both sides of the equation.

x=2

x=2

Set the next factor equal to 0.

x+5=0

Subtract 5 from both sides of the equation.

x=-5

x=-5

The final solution is all the values that make (x-2)(x+5)=0 true.

x=2,-5

Solve Using the Square Root Property x^2-10=-3x